(untitled) (Bangladesh Journal of Animal Science, 2017)
Bangladesh, a country of 147,570 Km2, had a total human population of 144.0 million in 2011 which is estimated as 160 million in 2015. Livestock that includes cattle, buffalo, goat and sheep and poultry such as, chicken, ducks and pigeons are important to her food and agriculture. Their total population according to Agricultural Census (2008) is 25.67, 0.54, 16.3, 1.29, 97.8, 39.43 and 7.48 million, respectively. The objective of the study was to analyse the concentration of livestock and poultry and their proportional availability to humans of different regions and their distribution to different farm categories. The average distribution range of the above animals and poultry was 19.7 to 361.7, 0.39 to 15.4, 12.4 to 359, 0.3 to 43.0, 105 to 1212, 6 to 746 and 1.5 to 190 per square kilometre, respectively; and that of human population was 86.7 to 8229/Km2. Their distribution, comparing with that of human population, that excludes the use of non-habitable land for them, shows that the average range of each farm animal and poultry available in the country was 21 to 464, 0.28 to 32.3, 8.9 to 412, 1.4 to 46.6, 72.8 to 1875, 24 to 829, and 8.9 to 198 per 1000 people, respectively. The production areas of cattle were classified into four zones (Zone A, Zone B, Zone C and Zone D), and that of each of others into three zones (Zone A, Zone B, and Zone C). They were characterized using the socioeconomic attributes of their respective zone, and the geographic distribution map of each genotype was developed and reported. The Farm household rear 85.6%, 81.0%, 75.6%, 75.8%, 75.5%, 77.5%, and 82.2%, respectively, of the total population of the above animals and poultry, respectively; and the rest is kept by the Non-Farm households. The Non-Farm and the small households together rear 73.9%, 67.1%, 82.6%, 79.9%, 82.2%, 80.2%, and 70.3%, respectively, and this shows that livestock and poultry; in addition to the production of milk, meat and eggs; support livelihood improvement of the land poor farmer in the country. However, the database of animal sourced foods (ASF) produced by them in different regions, their consumptions, wet marketing and the extent of value additions, availability of feeds and fodder, and health problems in addition to regional planning for mitigation of climate pollution of animal origin are utmost concerns for doubling of livestock and poultry production and productivity by 2030. Bang. J. Anim. Sci. 2017. 46 (1): 65-81